Commercialization of University Research Products and its Outcome on University Performance - Putit, Lennora; Hasan, Hazmilah; Ahmad Suki, Amirah; Shahbodin, Faaizah (2014)
Developing and commercializing new products are necessities for any organizations to remain competitive in the marketplace. This study aims to determine factors affecting commercialization of new research products and its outcome on university performance. Several constructs such as innovation, communication, supply chain management (SCM) efficiency, product commercialization, and university performance are applied in this study. Using quota sampling approach, a total of 350 self–administered survey questionnaires were distributed to target respondents from public universities with only 280 returned usable feedback. Data analysis was subsequently carried out using Statistical Package for Social Science (SPSS) version 20.0. Regression results reveal that all innovation, communication and SCM are significant predictors of new research product commercialization. In turn, commercialization significantly impacts a university’s performance. Several managerial implications could be further observed from this study.